Síntese de derivados de D-galactose inibidores potenciaisde interação lectina-carboidrato - Diogo Teixeira Carvalho (2008)
Lectins are proteins involved in carbohydrate recognition and their interaction is important in many natural and pathogenic events, as immunological response, fertilization, embryogenesis, infection and cancer metastasis. Hence, studies aimed at antiadhesion therapy with natural and synthetic mono- or multivalent carbohydrate derivatives showpromising results, mainly in infectious diseases. Herein is described the synthesis and spectrometric characterization of nineteen new substances in a total of thirty D-galactose derivatives: one galactosyl azide, two galactosyl amides, three galactosyl sulfonamides,twelve aryl galactosides and a series of seven methoxycarbonylphenyl galactosides derivatives obtained by modification at C-6 position. These substances were obtained in good yields and were evaluated in two biological assays, the Erythrina cristagalli-induced hemagglutination assay and the inhibition of erythrophagocytosis by Entamoeba histolyticatrofozoites assay. These processes are mediated by D-galactose and D-galactose/Nacetyl- D-galactosamine specific lectins, respectively. Although most D-galactose derivatives were not good enough as inhibitors of hemagglutination process, some aryl galactosides showed an eight-fold increase in potency when compared to D-galactose. Inthe erythrophagocytosis inhibition assay, most of tested substances were not active, except one amine, the isopropyl derivative, which reduced erythrophagocytosis in 65%